Youtube's utilization in moderate religious education for children: An analysis of digital parenting behavior among millennial couples - Fatimatul Wardah, Nuril; Fihris; Nasirudin; Nasikhin; Aang Kunaepi (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2026)
Background: Advances in digital technology have changed the way millennial parents instill religious education in their children. YouTube is the main platform for transmitting religious values. However, the existence of extremist and non-moderate content raises concerns about children's exposure to misunderstood, intolerant, and age-inappropriate religious beliefs. Objective: This study analyzes the role of YouTube as a medium of moderate religious education in the digital parenting practices of millennial couples in Landungsari, Pekalongan City, Indonesia. Methods: The research used a qualitative approach with a case study design. Data were obtained through in-depth interviews, participant observations, and content documentation, and analyzed using the Miles and Huberman models. Results: Millennial parents actively use YouTube for moderate religious education, prioritizing content such as Nussa & Rara animations and the KABI channel, accompanied by live mentoring and limiting watch time to 30-45 minutes per session. However, YouTube's unpredictable algorithm is a major obstacle in maintaining the consistency of moderate content. Conclusion: YouTube has the potential to become a moderate religious education medium if supported by planned digital parenting. The study provides an empirical foundation for strengthening Muslim families' digital media literacy and fostering a moderate and child-friendly religious content ecosystem.